(untitled) (Fiep Bulletin - online, 2014)
This article presents and discusses the continual formation of the Physical Education Teachers by examining the extension courses offered by the Second Time Program. The theoretical and practical concepts involved in the formation and communication in the Physical Education area are thought over in the presentation of these courses.